Edukasi Therapi Mindfulness Spritual pada Orang Dengan HIV dan AIDS (ODHA) - Yuliana Yuliana; Giat Wantoro; Ratu Kusuma; Dwi Kartika Pebriyanti; Marnila Yesni; Rahmi Dwiyanti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
ODHA are people with HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome). Changes in the character of ODHA cannot be separated from psychological and social pressure and make many ODHA become depressed. The psychological and social pressure experienced by ODHA also has a negative impact so that ODHA become embarrassed, physically exhausted, limit their activities, are afraid, and don't know what to do in the future. The treatment used to deal with these problems is still based on cognitive therapy and has not been integrated with awareness of ODHA. Apart from that, the therapy carried out does not yet enable ODHA to be able to deal with the problems they experience in the long term. To overcome this problem, intervention is needed aimed at ODHA which is carried out independently based on self-awareness, namely spiritual mindfulness therapy. Mindfulness as a type of psychotherapy facilitated by nurses uses the concept of self-care theory where nurses become nursing agencies to facilitate the self-deficit experienced by ODHA who experience mental problems. Educational activities were carried out from December 2021 to February 2022, providing education to 23 participants for 30 minutes through lectures, discussions and questions and answers. Delivery of material using power point and leaflet media. During the activities carried out, the pre-test results were 6.04 and post-test 7.43. ODHA patients understand mindfulness therapy as an alternative therapy that calms emotions. The patient's response was feeling relieved and comfortable after participating in therapy.